Vitamin D deficiency and associated factors among Portuguese older adults - preliminary data from Nutrition UP 65 - Álvares, Luísa (2016)
INTRODUCTION: Background and aims: Recent studies show that vitamin D deficiency is a common problem among older adults. Data from European individuals report a prevalence of vitamin D deficiency up to 40%. However, data regarding Portuguese community dwelling elderly or living in care homes is lacking. This study aimed to identify vitamin D status and factors associated with vitamin D deficiency among a sample of Portuguese older adults within the Nutrition UP 65 study. Methods: A cluster sampling approach was used, representing Portuguese older adults according to age, sex, education level and regional area (NUTS). A cross sectional study was conducted. Vitamin D status was assessed by dosing 25(OH) D (calcidiol) serum levels and classified as normal ( 30 ng/mL), insufficient (20-29.9 ng/mL) or deficient (<20 ng/mL). A multivariable logistic regression model was conducted to identify factors associated with vitamin D deficiency andOdds Ratios (OR) and 95% Confidence Intervals (CI) were calculated. Results: From a sample size of 1500 participants, preliminary data from 361 older adults are available, 72.6% women, aged 65 years (39.6% aged 80 years). Frequency of vitamin D deficiency and insufficiency was 69.8% and 19.4%, respectively. After adjusting for potential confounders, factors associated with vitamin D deficiency were obesity, i.e., BMI 30.0 kg/m2, (OR=2.88, 95% CI: 1.41-5.88) and low gait speed (OR=1.85, 95% CI: 1.05-3.26). Besides, takingnutrient supplements decreased the odds of presenting vitamin D deficiency by 73% (OR= 0.27, 95% CI: 0.13-0.58). Conclusion: Vitamin D deficiency affects more than two thirds of this sample of Portuguese older adults. Being obese and presenting low gait speed are factors associated with vitamin D deficiency among this age group.